Study on Impact of Lean Six Sigma - Hui , Koay Boon; Sorooshian, Shahryar (Journal of Management and Science, 2017)
This paper purpose is to investigate the benefits of Lean Six Sigma to the Malaysian automotive industry. Lean is an approach that seeks to improve flow in the value stream and eliminate waste. It’s about doing things quickly. Six Sigma uses a powerful framework (DMAIC) and statistical tools to uncover root causes to understand and reduce variation. It’s about doing things right (defect free). As global competition continues to grow, the pressure to improve becomes more and more intense. Thus, a combination of both Lean and Six Sigma is born. This method provides an over-arching improvement philosophy that incorporates powerful data-driven tools to solve problems and create rapid transformational improvement at lower cost. Thus, this paper also tries to examine how the Lean Six Sigma can contribute and brings a positive impact to the automotive industry in Malaysia.